O livro didático numa relação dialógica : as atividades de compreensão textual como práticas discursivas - Moyses, Aline Maioli (2018)
The textbook has been, for some time, a study instrument used by the teacher and the student in the classroom. Since the implementation of the PNLD in 1996 of the National Curriculum Guidelines and Indicators, the selection of textbooks has been increasingly careful. In fact, having good teaching materials is important, but it is not enough. From this, it is relevant to problematize the criterion of selection and use of textbooks in classrooms, considering, above all, the reading activities proposed in them. The aim is to verify how the activities of textual comprehension present in the volume of the 6th grade of the book "Português Linguagens ", by William Cereja and Thereza Cochar (2015), of an Elementary School of Vitória, contribute to the discursive practices of the students as social subjects. Does this book reflect the proposals and themes covered by the manual? How do these activities influence students' discursive practices as active citizens / subjects in the society? Is the textbook the only instrument used by the teacher and the student? In graduation courses, is the teacher prepared to handle these books? These are some questions of this research. For its development, we analyzed the exercises of the book by Cereja and Cochar (2015), in order to verify the possible gaps that the activities of textual comprehension can generate, failing to stimulate the discursive practices and the construction of different meanings. From this analysis, we also investigated the representations of undergraduate teachers, trying to understand what they think about the textbook. The results of the research may contribute to the construction of a critical approach by both the learner and the teacher concerned to the activities proposed by the textbook, as well as to assist the new Portuguese teachers who will enter the classroom, with the selection of an adequate material for their own teaching practice.